Geochemistry of recent aragonite-rich sediments in Mediterranean karstic marine lakes: Trace elements as pollution and palaeoredox proxies and indicators of authigenic mineral formation. (February 2017) - Sondi, Ivan; Mikac, Nevenka; Vdović, Neda; Ivanić, Maja; Furdek, Martina; Škapin, Srečo D.
Abstract: This study investigates the geochemical characteristics of recent shallow-water aragonite-rich sediments from the karstic marine lakes located in the pristine environment on the island of Mljet (Adriatic Sea). Different trace elements were used as authigenic mineral formation, palaeoredox and pollution indicators. The distribution and the historical record of trace elements deposition mostly depended on the sedimentological processes associated with the formation of aragonite, early diagenetic processes governed by the prevailing physico-chemical conditions and on the recent anthropogenic activity. This study demonstrated that Sr could be used as a proxy indicating authigenic formation of aragonite in a marine carbonate sedimentological environment. Distribution of the redox sensitive elements Mo, Tl, U and Cd was used to identify changes in redox conditions in the investigated lake system and to determine the geochemical cycle of these elements through environmental changes over the last 100 years. The significant enrichment of these elements and the presence of early formed nanostructured authigenic framboidal pyrite in laminated deeper parts of sediment in Malo Jezero, indicate sporadic events of oxygen-depleted euxinic conditions in the recent past. Concentrations of trace elements were in the range characteristic for non-contaminated marine carbonates. However, the increase in the concentrations of Zn, Cu, Pb, Sn, Bi in the upper-most sediment strata of Veliko Jezero indicates a low level of trace element pollution, resulting from anthropogenic inputs over the last 40 years. The presence of butyltin compounds (BuTs) in the surface sediment of Veliko Jezero additionally indicates the anthropogenic influence in the recent past. Graphical abstract: Highlights: Sr was used as a proxy indicating authigenic formation of aragonite in marine sediments. Distribution of Mo, Tl, U and Cd indicate changes in redox conditions in core sediments. Mo, Tl, U and Cd are associated early formed nanostructured authigenic framboidal pyrite. Concentration of Zn, Cu, Pb, Sn and Bi in core sediments indicates a low level of pollution.